Positive pole piece, battery monomer, battery and electric device
Patent Information
- Application Number
- CN202380052758.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-24
- Publication Date
- 2025-04-25
AI Technical Summary
There are challenges in improving the cycle performance and energy density of lithium-ion batteries, especially the poor power performance of single-crystal cathode materials and the low mechanical strength and poor thermal stability of polycrystalline cathode materials, which lead to overvoltage of active materials in the battery during charge and discharge. and frequent ruptures, affecting the cycle performance of the battery.
The positive electrode sheet adopts a multi-layer structure. By adding additives (such as magnesium stearate, talc powder, micro-powder silica gel, etc.) to the first sub-layer with a large friction coefficient, the friction coefficient of the first sub-layer is reduced and the friction coefficient is reduced. The difference in pressure resistance of the second sub-layer due to the different friction coefficient of the material reduces the possibility of rupture of the active material and improves the wettability of the electrolyte and the cycle performance of the battery.
It effectively reduces the cracking phenomenon of active materials in the positive electrode plate, improves the cycle performance and energy density of the battery, and ensures the stability and efficiency of the battery during the charge and discharge process.
Smart Images

Figure CN119895580A_ABST
Abstract
Description
Positive electrode sheet, battery cell, battery and electrical device Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a positive electrode sheet, a battery cell, a battery, and an electrical device. Background Art
[0002] In recent years, lithium-ion batteries have been used in an increasingly diverse range of applications, including energy storage and power supply applications such as wind, hydro, thermal, and solar power plants, as well as in electric bicycles, electric motorcycles, electric vehicles, military equipment, and aerospace. While lithium-ion batteries have experienced significant development, higher demands have been placed on their cycle performance.
[0003] Therefore, how to improve the cycle performance of lithium-ion batteries is an urgent problem to be solved.
[0004] Summary of the Invention
[0005] The present application is made in view of the above-mentioned problems, and its purpose is to provide a positive electrode sheet, a battery cell, a battery and an electrical device, which improve the cycle performance of the battery cell.
[0006] The first aspect of the present application provides a positive electrode plate, comprising: a positive electrode current collector and a positive electrode film layer, the positive electrode film layer comprising multiple sublayers; a first sublayer among the multiple sublayers comprises a first positive electrode active material and an additive, and a second sublayer among the multiple sublayers comprises a second positive electrode active material; wherein the difference in friction coefficient between the first sublayer and the second sublayer is 0.1-0.3, optionally, 0.1-0.2.
[0007] In an embodiment of the present application, a positive electrode sheet includes a positive electrode current collector and a positive electrode film layer, wherein the positive electrode film layer includes multiple sublayers. Furthermore, a first sublayer and a second sublayer of the multiple sublayers each include a first positive electrode active material and a second positive electrode active material, wherein the friction coefficient of the first sublayer is greater than the friction coefficient of the second sublayer, with the difference between the friction coefficients being 0.1-0.3. Furthermore, the first sublayer includes an additive for reducing the friction coefficient of the first sublayer. By adding the additive to the first sublayer, which has a higher friction coefficient, the friction coefficient of the first sublayer can be reduced, the fluidity of the first positive electrode active material can be improved, and the difference in pressure resistance between the first and second sublayers due to the different friction coefficients can be reduced. In this way, when pressure is applied to the first and second sublayers to achieve an optimal compaction density, the second sublayer, which has a lower pressure resistance, is prevented from overpressurizing due to the significant difference in pressure resistance between the first and second sublayers. This reduces the likelihood of rupture of the second positive electrode active material and improves electrolyte wettability, thereby improving the battery's cycling performance.
[0008] In one possible embodiment, the additive includes at least one of magnesium stearate, talc, micro-powdered silica gel, polyethylene glycols, magnesium lauryl sulfate, boron nitride, niobium diselenide, calcium fluoride, and barium fluoride.
[0009] In an embodiment of the present application, by adding an additive that can reduce the friction coefficient of the first sub-layer with a larger friction coefficient, and by making the additive include at least one of magnesium stearate, talc, micro-powder silica gel, polyethylene glycol, magnesium lauryl sulfate, boron nitride, niobium diselenide, calcium fluoride, and barium fluoride, the friction coefficient of the first sub-layer can be effectively reduced, thereby improving the material fluidity of the first sub-layer.
[0010] In a possible implementation, the difference in friction coefficient between the first active material and the second active material is 0.1-0.8, or alternatively 0.2-0.5.
[0011] In the embodiment of the present application, the use of additives is to reduce the friction coefficient of the first sub-layer and reduce the difference in the pressure that multiple sub-layers can withstand, thereby reducing the probability of phenomena such as rupture of the active material in the positive electrode sheet. However, if the friction coefficient of the first positive electrode active material differs too much from that of the active materials in other sub-layers, the effect of using additives on reducing the difference in the friction coefficients of the multiple sub-layers is not obvious. By maintaining the difference in the friction coefficients of the first positive electrode active material and the second positive electrode active material at 0.1-0.8, especially 0.2-0.5, it can be ensured that after adding the additive to a certain sub-layer, the difference in the pressure that different sub-layers in the entire positive electrode sheet can withstand is reduced, thereby ensuring the normal function of the battery.
[0012] In a possible implementation, the friction coefficient of the first positive electrode active material is 0.8-1.5, and optionally 0.9-1.2.
[0013] In the embodiment of the present application, by making the friction coefficient of the first positive electrode active material 0.8-1.5, particularly 0.9-1.2, it is avoided that the friction coefficient of the first positive electrode active material is too large and thus causes the failure of the additive.
[0014] In a possible implementation, the friction coefficient of the second positive electrode active material is 0.4-0.8, optionally 0.5-0.8.
[0015] In the embodiment of the present application, by setting the friction coefficient of the second positive electrode active material to 0.4-0.8, particularly 0.5-0.8, the second sublayer formed by the second positive electrode active material having a certain friction coefficient can be better attached to other sublayers or the current collector.
[0016] In one possible embodiment, based on 100 parts by weight of the first sub-layer, the content of the additive is 0.3-10 parts by weight, or alternatively 0.5-3 parts by weight.
[0017] In the embodiment of the present application, the additive is added to the first sublayer with the largest friction coefficient among the multiple sublayers to reduce its friction coefficient, so the additive must be added in an appropriate amount. If the amount of the additive is too low, the improvement effect will be poor, and if the amount is too high, it will affect the energy density of the battery. By making the mass content of the additive in the first sublayer 0.3%-10%, especially 0.5%-3%, it is possible to reduce the possibility of rupture of the active material in a sublayer of the positive electrode sheet, thereby improving the cycle performance of the battery, and ensuring the energy density of the battery.
[0018] In one possible implementation, the volume distribution particle size Dv99 of the additive is no greater than four-fifths of the thickness of the first sub-layer.
[0019] In the embodiments of this application, if the additive particle size is too large, it can cause particle scratches, thereby affecting production efficiency. In severe cases, positive electrode material may accumulate in some areas, leading to lithium deposition. By ensuring that the volume distribution particle size Dv99 of the additive is no larger than four-fifths of the thickness of the first sublayer, the possibility of lithium deposition in the battery can be reduced.
[0020] In one possible embodiment, the volume distribution particle size Dv99 of the additive is not greater than three-fifths of the volume distribution particle size Dv50 of the first positive electrode active material.
[0021] In the embodiment of the present application, by ensuring that the volume distribution particle size Dv99 of the additive is no greater than three-fifths of the volume distribution particle size Dv50 of the first positive electrode active material, uneven distribution in the first sublayer due to excessive size of the additive can be avoided.
[0022] In a possible implementation manner, the first sublayer is the sublayer farthest from the positive electrode current collector among the multiple sublayers.
[0023] In the embodiment of the present application, by making the first sublayer the sublayer farthest from the positive electrode current collector among the multiple sublayers, it is beneficial to further reduce the pressure resistance difference of the multiple sublayers, and further reduce the possibility of rupture of active materials in other sublayers that require less pressure to reach the expected compaction density.
[0024] In a possible implementation manner, the mass ratio of the first sublayer to the second sublayer is 1:9-9:1, optionally 3:7-7:3.
[0025] In the embodiment of the present application, by maintaining the mass ratio of the first sublayer to the second sublayer at 1:9-9:1, particularly 3:7-7:3, the possibility of rupture of the active material in other sublayers requiring less pressure to reach the expected compaction density can be further reduced.
[0026] In one possible embodiment, the compaction density of the positive electrode sheet is 2.0-3.5 g / cm 3 , optionally 2.5-3.2 g / cm 3 .
[0027] In the embodiment of the present application, the compaction density of the positive electrode sheet is 2.0-3.5g / cm 3 , especially 2.5- 3.2g / cm 3 , which can not only ensure the energy density of the battery, but also improve the cycle performance of the battery.
[0028] In a possible embodiment, the compaction density of the first sub-layer is 3.0-4.0 g / cm 3 , optionally 3.2-3.6 g / cm 3 .
[0029] In the embodiment of the present application, the compaction density of the first sub-layer is 3.0-4.0 g / cm 3 , especially 3.2-3.6g / cm 3 , which can not only ensure the energy density of the battery, but also improve the cycle performance of the battery.
[0030] In one possible embodiment, the compacted density of the second sub-layer is 2.2-3.5 g / cm 3 , optionally 2.5-3.0 g / cm 3 .
[0031] In the embodiment of the present application, the compaction density of the second sub-layer is 2.2-3.5 g / cm 3 , especially 2.5-3.0g / cm 3 , which can not only ensure the energy density of the battery, but also improve the cycle performance of the battery.
[0032] In a possible implementation, the thickness of the positive electrode film layer is 45-100 μm, optionally 50-85 μm.
[0033] In the embodiment of the present application, by making the thickness of the positive electrode film layer 45-100 μm, especially 50-85 μm, the probability of difficulty in electrolyte infiltration due to excessive thickness of the film layer can be reduced, and the energy density of the battery can be ensured.
[0034] In a possible implementation manner, the thickness of the first sub-layer is 5-90 μm, optionally 20-75 μm.
[0035] In the embodiment of the present application, by setting the thickness of the first sub-layer to 5-90 μm, especially 20-75 μm, the probability of difficulty in electrolyte infiltration due to excessive thickness of the sub-layer can be reduced while ensuring the energy density of the battery.
[0036] In a possible implementation manner, the thickness of the second sub-layer is 4-60 μm, optionally 10-50 μm.
[0037] In the embodiment of the present application, by setting the thickness of the second sub-layer to 4-60 μm, especially 10-50 μm, the probability of difficulty in electrolyte infiltration due to excessive thickness of the sub-layer can be reduced while ensuring the energy density of the battery.
[0038] In one possible embodiment, the first positive electrode active material includes a layered transition metal oxide, optionally including Li x (Ni a Co b Mn c ) 1-d M d O 2-y A y , wherein M includes at least one of Zr, Al, B, Ta, Mo, W, Nb, Sb, and La, 0.2<x≤1.2, 0.5≤a<1.0, 0≤b<0.5, 0≤c<1, 0≤d<1, and 0≤y<0.02.
[0039] In one possible embodiment, the second positive electrode active material includes an olivine-structured lithium phosphate Li e Fe 1-x-y Mn x M' y P 1-m C m O 4-n D n , 0<e≤1.1, 0≤x≤1, 0≤y<1, 0≤x+y≤1, 0≤m≤0.1, 0≤n≤0.4, M' includes at least one of other transition metal elements or non-transition metal elements except Fe and Mn; optionally, M' includes at least one of Cr, Mg, Ti, Al, Zn, W, Nb, and Zr; optionally, the lithium-containing phosphate with an olivine structure includes at least one of lithium iron phosphate, lithium manganese phosphate, and lithium manganese iron phosphate.
[0040] The second aspect of the present application provides a battery cell, comprising the positive electrode sheet described in any embodiment of the first aspect of the present application.
[0041] A third aspect of the present application provides a battery, comprising the battery cell described in the second aspect of the present application.
[0042] A fourth aspect of the present application provides an electrical device, comprising the battery according to the third aspect of the present application, wherein the battery is used to provide electrical energy. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following is a brief introduction to the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.
[0044] FIG1 is a schematic structural diagram of a positive electrode sheet according to an embodiment of the present application;
[0045] FIG2 is a schematic diagram of a battery cell according to an embodiment of the present application;
[0046] FIG3 is a schematic structural diagram of a battery cell according to an embodiment of the present application;
[0047] FIG4 is a schematic diagram of a battery according to an embodiment of the present application;
[0048] FIG5 is a schematic structural diagram of a battery according to an embodiment of the present application;
[0049] FIG6 is a schematic structural diagram of an electric device according to an embodiment of the present application. DETAILED DESCRIPTION
[0050] The following describes in detail embodiments of the electrode assembly, battery cell, battery, and electrical device of the present application, with appropriate reference to the accompanying drawings. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of substantially identical structures may be omitted. In addition, the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0051] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of specific range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0052] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0053] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0054] Unless otherwise specified, all steps of the present application may be performed sequentially, randomly, or optionally sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b), and (c), or may include steps (a), (c), and (b), or may include steps (c), (a), and (b), etc.
[0055] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.
[0056] The terms "above", "below", "greater than" or "less than" as used in this application are inclusive of the number, for example, "at least one" means one or more, and "at least one of A and B" means "A", "B" or "A and B".
[0057] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0058] Lithium batteries are widely used in consumer electronics due to their high energy density, high power, and long cycle life. In recent years, with the continuous development of electric vehicles and energy storage systems, the demand for battery cycle performance and energy density has also continued to increase. Therefore, the development of large-scale energy storage systems with long cycle life and high energy density is particularly important.
[0059] In order to improve the energy density of lithium batteries and overcome the problems of poor power performance of single crystal positive electrode materials and low mechanical strength, poor thermal stability and poor cycle performance of polycrystalline positive electrode materials in the prior art, the current common practice is to mix the two so that the two can complement each other's advantages, so that the multi-element active material composed of single crystal particles and polycrystalline particles has both the high compaction density, stable structure and good safety performance of single crystal materials, while taking into account the advantages of small particle polycrystalline materials such as high capacity and good power output. However, in such a mixed active material of single crystal and polycrystalline, it is usually necessary to apply a certain pressure to the mixed active material so that the active material reaches a certain compaction density. In this way, the single crystal and polycrystalline materials will cause one of the materials to be over-pressurized due to the difference in compressive strength, and then the active material will rupture, etc., which will ultimately affect the cycle performance of the battery. Therefore, how to make the battery take into account both high energy density and long cycle performance is an urgent problem to be solved.
[0060] In view of this, the present application provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode film layer, wherein the positive electrode film layer comprises multiple sublayers. An additive for reducing the friction coefficient is added to the first sublayer, which has the highest friction coefficient among the multiple sublayers. This can reduce the difference in pressure resistance between the first sublayer and the other sublayers due to the different friction coefficients of the materials, thereby reducing the possibility of rupture of active materials in the positive electrode film layer due to overpressure, thereby improving the cycle performance of the battery.
[0061] The positive electrode sheet, battery cell, battery and electrical device of the present application are described below with reference to the accompanying drawings.
[0062] In addition, the technical solution of the present application is applicable to various types of batteries such as lithium-ion batteries, lithium metal batteries, sodium-ion batteries, etc., and the present application does not limit this; for the sake of description, the following description will take lithium-ion batteries as an example.
[0063] [Positive electrode]
[0064] In a first aspect, the present application provides a positive electrode sheet. Figure 1 is a schematic structural diagram of a positive electrode sheet according to one embodiment of the present application. As shown in Figure 1, the positive electrode sheet includes a positive electrode current collector 121 and a positive electrode film 122. The positive electrode film 122 includes multiple sublayers. A first sublayer 123 of the multiple sublayers includes a first positive electrode active material and an additive. A second sublayer 124 of the multiple sublayers includes a second positive electrode active material. The difference in friction coefficient between the first sublayer 123 and the second sublayer 124 is 0.1-0.3, and optionally 0.1-0.2.
[0065] In the embodiment of the present application, the multiple sub-layers are no less than two sub-layers; that is, there can be two sub-layers, or three sub-layers, etc. The present application does not limit this, and the following embodiments are only described with two sub-layers.
[0066] Research has found that in the positive electrode sheet of a multi-layer structure, adding an additive for reducing the friction coefficient of a sub-layer with the largest friction coefficient can reduce the difference in the compressive resistance of different sub-layers, thereby reducing the probability of overpressure and rupture of the active material in the positive electrode sheet.
[0067] Typically, a battery cell consists of a positive electrode, a separator, a negative electrode, and an electrolyte. During the battery's charge and discharge processes, active ions are embedded in and extracted from the positive and negative electrodes. The electrolyte conducts ions between the positive and negative electrodes. The separator, located between the positive and negative electrodes, primarily prevents short circuits while allowing ions to pass through.
[0068] It should be noted here that the “positive electrode sheet” and “negative electrode sheet” mentioned in the embodiments of the present application refer to the positive electrode sheet and the negative electrode sheet as a whole including active materials, current collectors or other additives.
[0069] The positive electrode sheet includes a positive electrode current collector 121 and a positive electrode film layer 122 disposed on at least one surface of the positive electrode current collector 121 , wherein the positive electrode film layer 122 includes a positive electrode active material.
[0070] As an example, the positive electrode current collector 121 has two opposite surfaces in its thickness direction, and the positive electrode film layer 122 is disposed on either or both of the two opposite surfaces of the positive electrode current collector 121 .
[0071] In the above scheme, the positive electrode sheet includes a positive electrode current collector 121 and a positive electrode film layer 122. The positive electrode film layer 122 includes multiple sublayers. Furthermore, the first sublayer 123 and the second sublayer 124 of the multiple sublayers each include a first positive electrode active material and a second positive electrode active material. The friction coefficient of the first sublayer 123 is greater than the friction coefficient of the second sublayer 124, and the difference between the two friction coefficients is 0.1-0.3. In addition, the first sublayer 123 includes an additive for reducing the friction coefficient of the first sublayer 123. By adding the additive to the first sublayer 123, where the first positive electrode active material with a higher friction coefficient is located, the friction coefficient of the first sublayer 123 can be reduced and the fluidity of the first positive electrode active material can be improved, thereby reducing the difference in the pressure that the first sublayer 123 and the second sublayer 124 can withstand due to the different friction coefficients of the materials. In this way, when pressure is applied to the first sublayer 123 and the second sublayer 124 to achieve a better compaction density of the two sublayers, the second sublayer 124 with smaller compressive resistance will not be over-pressured due to the large difference in compressive resistance between the first sublayer 123 and the second sublayer 124, thereby reducing the possibility of rupture of the second positive electrode active material and improving the wettability of the electrolyte, thereby improving the cycle performance of the battery.
[0072] In some embodiments, the additive includes at least one of magnesium stearate, talc, micronized silica gel, polyethylene glycols, magnesium lauryl sulfate, boron nitride, niobium diselenide, calcium fluoride, and barium fluoride.
[0073] In the embodiment of the present application, the additive may be a dry solid lubricant, or a substance having a lamellar structure with parallel atoms.
[0074] Specifically, the additive includes at least one of magnesium stearate, talc, micro-powdered silica gel, polyethylene glycol, magnesium lauryl sulfate, boron nitride, niobium diselenide, calcium fluoride, and barium fluoride.
[0075] In some embodiments, the difference in friction coefficient between the first positive electrode active material and the second positive electrode active material is 0.1-0.8, or alternatively 0.2-0.5.
[0076] In the above scheme, the use of additives is to reduce the friction coefficient of the first sublayer 123 and reduce the difference in the pressure that multiple sublayers can withstand, thereby reducing the probability of phenomena such as rupture of the active material in the positive electrode sheet. However, if the friction coefficient of the first positive electrode active material differs too much from that of the active materials in other sublayers, the effect of using additives on reducing the difference in the friction coefficients of the multiple sublayers is not obvious. By maintaining the difference in the friction coefficients of the first positive electrode active material and the second positive electrode active material at 0.1-0.8, especially 0.2-0.5, it can be ensured that after adding the additive to a certain sublayer, the difference in the pressure that different sublayers in the entire positive electrode sheet can withstand is reduced, thereby ensuring the normal function of the battery.
[0077] In some embodiments, the friction coefficient of the first positive electrode active material is 0.8-1.5, optionally 0.9-1.2.
[0078] In the above solution, by making the friction coefficient of the first positive electrode active material 0.8-1.5, especially 0.9-1.2, failure of the additive caused by excessively large friction coefficient of the first positive electrode active material is avoided.
[0079] In some embodiments, the friction coefficient of the second positive electrode active material is 0.4-0.8, optionally 0.5-0.8.
[0080] In the above solution, by setting the friction coefficient of the second positive active material to 0.4-0.8, particularly 0.5-0.8, the second sublayer 124 formed by the second positive active material having a certain friction coefficient can be better attached to other sublayers or the current collector.
[0081] In some embodiments, based on 100 parts by weight of the first sub-layer 123 , the content of the additive is 0.3-10 parts by weight, or alternatively 0.5-3 parts by weight.
[0082] In the above scheme, the additive is added to the first sublayer 123, which has the highest friction coefficient among the multiple sublayers, to reduce its friction coefficient. Therefore, the additive must be added in an appropriate amount. If the amount of the additive is too low, the improvement effect will be poor. If the amount is too high, it will affect the energy density of the battery. By setting the content of the additive in the first sublayer 123 to 0.3%-10%, especially 0.5%-3%, the possibility of rupture of the active material in a sublayer of the positive electrode sheet can be reduced, thereby improving the cycle performance of the battery, and ensuring the energy density of the battery.
[0083] In some embodiments, the volume distribution particle size Dv99 of the additive is no greater than four-fifths of the thickness of the first sub-layer 123 .
[0084] In the examples of the present application, Dv99 refers to the particle size of 99% of the volume distribution of the additive.
[0085] In the above solution, if the additive particle size is too large, it can cause particle scratches, thereby affecting production efficiency. In severe cases, positive electrode material may accumulate in some areas, leading to lithium deposition. By ensuring that the volume distribution particle size Dv99 of the additive is no greater than four-fifths of the thickness of the first sublayer 123, the possibility of lithium deposition in the battery can be reduced.
[0086] In some embodiments, the volume distribution particle size Dv99 of the additive is no greater than three-fifths of the volume distribution particle size Dv50 of the first positive electrode active material.
[0087] In the above solution, by ensuring that the volume distribution Dv99 of the additive is no greater than three-fifths of the volume distribution particle size Dv50 of the first positive electrode active material, uneven distribution in the first sublayer 123 due to excessive size of the additive can be avoided.
[0088] In some embodiments, the first sublayer 123 is the sublayer farthest from the positive electrode current collector 121 among the multiple sublayers.
[0089] In the above scheme, by making the first sublayer 123 the sublayer farthest from the positive electrode current collector 121 among the multiple sublayers, it is beneficial to further reduce the pressure resistance difference of the multiple sublayers and further reduce the possibility of rupture of the active material in other sublayers that require less pressure to reach the expected compaction density.
[0090] In some embodiments, the mass ratio of the first sublayer 123 to the second sublayer 124 is 1:9-9:1, or alternatively 3:7-7:3.
[0091] In the above solution, by maintaining the mass ratio of the first sublayer 123 to the second sublayer 124 at 1:9-9:1, particularly 3:7-7:3, the possibility of cracking of the active materials in other sublayers requiring less pressure to reach the expected compaction density can be further reduced.
[0092] In some embodiments, the compacted density of the positive electrode sheet is 2.0-3.5 g / cm 3 , optionally 2.5-3.2 g / cm 3 .
[0093] In the above scheme, the compaction density of the positive electrode sheet is 2.0-3.5g / cm 3 , especially 2.5-3.2g / cm 3 , which can not only ensure the energy density of the battery, but also improve the cycle performance of the battery.
[0094] In some embodiments, the compacted density of the first sub-layer 123 is 3.0-4.0 g / cm 3 , optionally 3.2-3.6 g / cm 3 .
[0095] In the above solution, the compaction density of the first sub-layer 123 is 3.0-4.0 g / cm 3 , especially 3.2-3.6g / cm 3 , which can not only ensure the energy density of the battery, but also improve the cycle performance of the battery.
[0096] In some embodiments, the second sub-layer 124 has a compacted density of 2.2-3.5 g / cm 3 , optionally 2.5-3.0 g / cm 3 .
[0097] In the above solution, the compaction density of the second sub-layer 124 is 2.2-3.5 g / cm 3 , especially 2.5-3.0g / cm 3 , which can not only ensure the energy density of the battery, but also improve the cycle performance of the battery.
[0098] In some embodiments, the thickness of the positive electrode film layer 122 is 45-100 μm, optionally 50-85 μm.
[0099] In the above solution, by making the thickness of the positive electrode film layer 122 45-100 μm, especially 50-85 μm, the probability of difficulty in electrolyte infiltration due to excessive thickness of the film layer can be reduced while ensuring the energy density of the battery.
[0100] In some embodiments, the thickness of the first sub-layer 123 is 5-90 μm, optionally 20-75 μm.
[0101] In the above solution, by making the thickness of the first sub-layer 123 5-90 μm, especially 20-75 μm, the probability of difficulty in electrolyte infiltration due to excessive thickness of the sub-layer can be reduced while ensuring the energy density of the battery.
[0102] In some embodiments, the second sub-layer 124 has a thickness of 4-60 μm, or alternatively 10-50 μm.
[0103] In the above solution, by setting the thickness of the second sub-layer 124 to 4-60 μm, especially 10-50 μm, the probability of difficulty in electrolyte infiltration due to excessive thickness of the sub-layer can be reduced while ensuring the energy density of the battery.
[0104] In some embodiments, the first cathode active material comprises a layered transition metal oxide, optionally comprising Li x (Ni a Co b Mn c ) 1-d M d O 2-y A y , wherein M includes at least one of Zr, Al, B, Ta, Mo, W, Nb, Sb, and La, 0.2<x≤1.2, 0.5≤a<1.0, 0≤b<0.5, 0≤c<1, 0≤d<1, and 0≤y<0.02.
[0105] In some embodiments, the second positive active material includes a lithium-containing phosphate Li including an olivine structure. e Fe 1-x-y Mn x M'y P 1-m C m O 4-n D n , 0<e≤1.1, 0≤x≤1, 0≤y<1, 0≤x+y≤1, 0≤m≤0.1, 0≤n≤0.4, M' includes at least one of other transition metal elements or non-transition metal elements except Fe and Mn; optionally, M' includes at least one of Cr, Mg, Ti, Al, Zn, W, Nb, and Zr; optionally, the lithium-containing phosphate with an olivine structure includes at least one of lithium iron phosphate, lithium manganese phosphate, and lithium manganese iron phosphate.
[0106] It should be noted here that during the charge and discharge process of the battery (the battery voltage is usually between 2-5V), as Li ions are continuously deintercalated and consumed, the molar content of Li in the battery is different when it is discharged to different states. The above definition of x includes the molar content of Li in different charge and discharge states of the battery.
[0107] In some embodiments, the positive electrode current collector 121 may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0108] In some embodiments, the positive electrode active material may also adopt the positive electrode active material for batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM333), LiNi 0.5 Co 0.2 Mn 0.3O2 (also referred to as NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM811), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds. Examples of olivine-structured lithium-containing phosphates may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0109] In some embodiments, the positive electrode film layer 122 may further include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorine-containing acrylate resin.
[0110] In some embodiments, the positive electrode film layer 122 may further include a conductive agent. For example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0111] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the second positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a second positive electrode slurry, and the second positive electrode slurry is coated on the positive electrode collector 121; the first positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a first positive electrode slurry, and the first positive electrode slurry is coated on the second positive electrode active material layer. After drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0112] [Negative electrode]
[0113] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer provided on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0114] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0115] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0116] In some embodiments, the negative electrode active material may be a negative electrode active material for a battery that is well known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxides, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxides, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0117] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0118] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0119] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0120] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0121] [Electrolyte]
[0122] The electrolyte plays a role in conducting ions between the positive electrode and the negative electrode. In the embodiment of the present application, the electrolyte includes the first electrolyte salt, the second electrolyte salt and the third electrolyte salt described in any of the above embodiments.
[0123] In some embodiments, the electrolyte further comprises a solvent. The solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.
[0124] In some embodiments, the electrolyte may optionally include negative electrode film-forming additives, positive electrode film-forming additives, and may also include performance additives that can improve certain battery properties, such as improving battery overcharge performance, improving battery high or low temperature performance, etc.
[0125] [Isolation film]
[0126] In some embodiments, the battery cell 100 further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.
[0127] In some embodiments, the material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0128] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into the electrode assembly 12 by a winding process or a lamination process.
[0129] In some embodiments, the battery cell 100 may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.
[0130] In some embodiments, the outer packaging of the battery cell 100 may be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. Alternatively, the outer packaging of the battery cell 100 may be a soft shell, such as a pouch-type soft shell. The soft shell may be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0131] The present application has no particular limitation on the shape of the battery cell 100 , which may be cylindrical, square, or any other shape. For example, FIG2 is a schematic diagram of a battery cell according to an embodiment of the present application.
[0132] Figure 3 is a schematic structural diagram of a battery cell according to an embodiment of the present application. As shown in Figure 3, the outer packaging may include a shell 11 and a cover plate 13. The shell 11 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 11 has an opening connected to the receiving cavity, and the cover plate 13 can be covered on the opening to close the receiving cavity. The positive electrode, the negative electrode and the solid electrolyte can form an electrode assembly 12 through a winding process or a lamination process. The electrode assembly 12 is encapsulated in the receiving cavity. The number of electrode assemblies 12 contained in the battery cell 100 may be one or more, and those skilled in the art can select according to specific actual needs.
[0133] In some embodiments, the battery cells 100 may be assembled into a battery module. The battery module may contain one or more battery cells 100. The specific number may be selected by those skilled in the art based on the application and capacity of the battery module.
[0134] Figure 4 is a schematic diagram of a battery according to one embodiment of the present application, and Figure 5 is a schematic diagram of the structure of a battery according to one embodiment of the present application. Referring to Figures 4 and 5, a battery 400 may include a battery box and a plurality of battery cells 100 disposed within the battery box. The battery box includes an upper box body 401 and a lower box body 402. The upper box body 401 can be placed over the lower box body 402 to form an enclosed space for accommodating the battery cells 100. The plurality of battery cells 100 can be arranged in any manner within the battery box.
[0135] In addition, the present application also provides an electric device, which includes at least one of the positive electrode sheet, battery cell 100 or battery provided in the present application. The positive electrode sheet, battery cell 100, or battery can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but is not limited thereto.
[0136] For example, Figure 6 is a structural diagram of a vehicle according to an embodiment of the present application. As shown in Figure 6, vehicle 1 can be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A motor 500, a controller 600 and a battery 400 can be provided inside the vehicle 1, and the controller 600 is used to control the battery 400 to supply power to the motor 500. For example, a battery 400 can be provided at the bottom, front or rear of the vehicle 1. The battery 400 can be used to power the vehicle 1. For example, the battery 400 can be used as an operating power source for the vehicle 1, for the circuit system of the vehicle 1, for example, for the working power requirements during the start-up, navigation and operation of the vehicle 1. In another embodiment of the present application, the battery 400 can not only be used as an operating power source for the vehicle 1, but can also be used as a driving power source for the vehicle 1, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1.
[0137] As the electrical device, a positive electrode sheet, a battery cell 100 or a battery can be selected according to its usage requirements.
[0138] The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the electric device's requirements for high power and high energy density of the battery, a battery cell 100 or a battery can be used.
[0139] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be lightweight and thin, and may use the battery cell 100 as a power source.
[0140] [Example]
[0141] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.
[0142] [Example 1]
[0143] 1). Preparation of lithium-ion batteries
[0144] 1.1) Preparation of positive electrode
[0145] 1.11) First positive electrode active material: LiNi 0.5 Co 0.2 Mn 0.3O2 (LNCM), conductive agent acetylene black, binder, and micro-powder silica gel are dissolved in a solvent N-methylpyrrolidone (NMP) in a weight ratio of 96%:1%:2%:1%, and then fully stirred and mixed to prepare a first positive electrode active material; wherein, the particle size of micro-powder silica gel Dv99 / first positive electrode active material is 2 / 5, and the thickness of micro-powder silica gel Dv99 / first sublayer is 2 / 5;
[0146] 1.12) Second positive electrode active material: LiMn 0.5 Fe 0.5 PO4 (LMFP), conductive agent acetylene black, and binder are dissolved in solvent N-methylpyrrolidone (NMP) in a weight ratio of 97%:1%:2%, and the mixture is thoroughly stirred and mixed to prepare a second positive electrode active material;
[0147] 1.13) Positive electrode sheet: The second positive electrode active material is uniformly coated on the positive electrode current collector aluminum foil to obtain a second sublayer coated on the aluminum foil; the first positive electrode active material is uniformly coated on the second sublayer to form a first sublayer, which is then dried, cold pressed, and cut to obtain a positive electrode sheet in which the coating order is the first sublayer, the second sublayer, and the positive electrode current collector; wherein the mass ratio of the first sublayer to the second sublayer is 7:3.
[0148] 1.2) Preparation of negative electrode: Active material artificial graphite, conductive agent acetylene black, binder styrene-butadiene rubber (SBR), thickener sodium carboxymethyl cellulose (CMC) are thoroughly stirred and mixed in a suitable amount of deionized water solvent system at a weight ratio of 96.5%:0.7%:1.8%:1% to obtain negative electrode active material. The negative electrode active material is coated on Cu foil, and then dried, cold pressed, and cut to obtain negative electrode sheets.
[0149] 1.3) Preparation of diaphragm: PE porous polymer film is used as the isolation membrane.
[0150] 1.4) Electrolyte: Dissolve EC / EMC / DMC in 1M LiPF6 at a volume ratio of 1:1:1 and stir evenly.
[0151] 1.5) Assembly: The positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator positioned between the positive and negative electrodes to provide separation. Winding is done to form an electrode assembly, and electrolyte is added. The lithium-ion battery is then hot-pressed at 100°C and 250 MPa for 2 minutes.
[0152] [Example 2]
[0153] The preparation process of the lithium-ion battery of Example 2 is substantially the same as that of Example 1, except that the mass ratio of the first sublayer to the second sublayer is 6:4.
[0154] [Example 3]
[0155] The preparation process of the lithium-ion battery of Example 3 is basically the same as that of Example 1, except that the LiNi in the first positive electrode active material is 0.5 Co 0.2 Mn 0.3 O2 (LNCM), conductive agent acetylene black, binder, and micro-powder silica gel are dissolved in solvent N-methylpyrrolidone (NMP) in a weight ratio of 96.7%:1%:2%:0.3%.
[0156] [Example 4]
[0157] The preparation process of the lithium-ion battery of Example 4 is basically the same as that of Example 1, except that the LiNi in the first positive electrode active material is 0.5 Co 0.2 Mn 0.3 O2 (LNCM), conductive agent acetylene black, binder, and micro-powder silica gel are dissolved in solvent N-methylpyrrolidone (NMP) in a weight ratio of 87%:1%:2%:10%.
[0158] [Example 5]
[0159] The preparation process of the lithium-ion battery of Example 5 is basically the same as that of Example 1, except that the particle size of the micro-powder silica gel Dv99 / the first positive electrode active material is 3 / 5.
[0160] [Example 6]
[0161] The preparation process of the lithium-ion battery of Example 6 is basically the same as that of Example 1, except that the thickness of the micro-powder silica gel Dv99 / first sub-layer is 4 / 5.
[0162] [Example 7]
[0163] The preparation process of the lithium-ion battery of Example 7 is substantially the same as that of Example 1, except that the micropowder silica gel in the first positive electrode active material is replaced with boron fluoride.
[0164] [Example 8]
[0165] The preparation process of the lithium-ion battery of Example 8 is basically the same as that of Example 7, except that the particle size of boron fluoride Dv99 / the first positive electrode active material is 1 / 5.
[0166] [Example 9]
[0167] The preparation process of the lithium-ion battery of Example 9 is basically the same as that of Example 7, except that the thickness of the boron fluoride Dv99 / first sublayer is 1 / 5.
[0168] [Example 10]
[0169] The preparation process of the lithium-ion battery of Example 10 is substantially the same as that of Example 1, except that the silica gel powder in the first positive electrode active material is replaced with calcium fluoride.
[0170] [Example 11]
[0171] The preparation process of the lithium-ion battery of Example 11 is substantially the same as that of Example 10, except that the particle size of calcium fluoride Dv99 / first positive electrode active material is 3 / 5.
[0172] [Example 12]
[0173] The preparation process of the lithium-ion battery of Example 12 is basically the same as that of Example 10, except that the thickness of calcium fluoride Dv99 / first sublayer is 3 / 10.
[0174] [Example 13]
[0175] The preparation process of the lithium-ion battery of Example 13 is basically the same as that of Example 1, except that the second positive electrode active material is replaced by lithium iron phosphate instead of lithium manganese iron phosphate.
[0176] [Example 14]
[0177] The preparation process of the lithium-ion battery of Example 14 is basically the same as that of Example 1, except that the particle size of the micropowder silica gel Dv99 / the first positive electrode active material is 7 / 5.
[0178] [Example 15]
[0179] The preparation process of the lithium-ion battery of Example 15 is basically the same as that of Example 1, except that the thickness of the micro-powder silica gel Dv99 / first sub-layer is 6 / 5.
[0180] [Example 16]
[0181] The preparation process of the lithium-ion battery of Example 16 is basically the same as that of Example 1, except that the LiNi in the first positive electrode active material is 0.5 Co 0.2 Mn 0.3 O2 (LNCM), conductive agent acetylene black, binder, and micro-powder silica gel are dissolved in solvent N-methylpyrrolidone (NMP) in a weight ratio of 96.8%:1%:2%:0.2%.
[0182] [Example 17]
[0183] The preparation process of the lithium-ion battery of Example 17 is basically the same as that of Example 1, except that the LiNi in the first positive electrode active material is 0.5 Co 0.2 Mn 0.3O2 (LNCM), conductive agent acetylene black, binder, and micro-powder silica gel are dissolved in solvent N-methylpyrrolidone (NMP) in a weight ratio of 85%:1%:2%:12%.
[0184] [Comparative Example 1]
[0185] The preparation process of the lithium ion battery of Comparative Example 1 is basically the same as that of Example 1, except that the LiNi in the first positive electrode active material is 0.5 Co 0.2 Mn 0.3 O2 (LNCM), conductive agent acetylene black, and binder are dissolved in solvent N-methylpyrrolidone (NMP) in a weight ratio of 97%:1%:2%.
[0186] 2) Performance characterization of lithium-ion battery positive electrode
[0187] 2.1) Measurement of compacted density: Take the prepared positive electrode sheet and cut a section with a circular or square cutter. Measure the thickness and weigh it. Wash the negative electrode material with an acetone-alcohol mixture and dry it. Weigh and measure the mass and thickness of the remaining Al foil. Divide the difference between the two weights by the area to calculate the areal density. Divide the areal density by the thickness difference to obtain the compacted density.
[0188] 2.2) Friction coefficient measurement: Referring to GB / T 22895-2008, take two coated positive electrode sheets as an example (if the friction coefficient of the first positive electrode active material is measured, only the first positive electrode active material, binder, and conductive agent are coated on the positive electrode sheet; similarly, if the friction coefficient of the first sub-layer with the additive added is measured, the first positive electrode active material, additive, binder, and conductive agent are coated on the positive electrode sheet). Weigh the mass m of one of the positive electrode sheets, place the two positive electrode sheets together in planar contact, and apply uniform contact pressure (with the weighed sheet on top). Drag the upper sheet at a speed of 20 mm / s, and record the force F required for initial sliding. The friction coefficient μ can then be calculated according to the formula: μ = F / (m×g); where g is the acceleration due to gravity, typically 9.8 m / s. 2 .
[0189] 2.2) Measurement of volume distribution particle size Dv99 and volume distribution particle size Dv50: Particle size distribution laser diffraction method according to GB / T19077-2016 can be used for testing using a laser particle size analyzer (e.g., Master Size 3000).
[0190] Table 1 Specific parameters of Examples 1-17 and Comparative Example 1
[0191] 3) Performance characterization of lithium-ion batteries
[0192] 3.1) Cycling Performance: At room temperature, maintain the battery charge and discharge voltage range between 2.5-4.35V, cycle at a current density of 1C, and record the number of cycles at which the capacity retention rate decays to 80%. See Table 2 for test results.
[0193] 3.2) Energy Density: At room temperature, charge the battery to 4.35V at a current density of 0.5C, then discharge it to 2.5V. Record the energy density during discharge. Repeat this process three times and calculate the average discharge energy, E. Weigh the mass of the lithium-ion battery as M, and calculate the energy density, GED, of the lithium-ion battery as E / M. Using the GED1 of the lithium-ion battery in Comparative Example 1 as a reference, the energy density, GED2, of the lithium-ion batteries in the remaining examples is GED2 / GED1. See Table 2 for the measurement results.
[0194] Table 2 Performance test of lithium ion batteries of Examples 1-17 and Comparative Example 1
[0195] Combining Examples 1-17 and Comparative Example 1, it can be seen that after adding an additive for reducing the friction coefficient to the first sublayer with a larger friction coefficient, the friction coefficient of the first sublayer is significantly reduced, and the cyclability of the lithium-ion battery can be improved.
[0196] It can be seen from Examples 1-6, 7-9 and 10-12 that various types of additives can improve the cycle performance of lithium-ion batteries.
[0197] In combination with Examples 1-17 and Comparative Example 1, it can be seen that after adding an additive for reducing the friction coefficient to the first sublayer with a larger friction coefficient, the friction coefficient of the first sublayer is significantly reduced, which can improve the cycle performance of the lithium-ion battery; in combination with Examples 1-4 and Examples 16-17, it can be seen that maintaining the additive content at 0.3%-10% has a small effect on the energy density of the battery while improving the cycle performance of the lithium-ion battery; in combination with Examples 5-12 and Examples 14-15, it can be seen that maintaining the volume distribution particle size Dv99 of the additive at no more than three-fifths of the volume distribution particle size Dv50 of the first positive electrode active material and no more than four-fifths of the thickness of the first sublayer has a small effect on the energy density of the battery while improving the cycle performance of the lithium-ion battery.
[0198] Combining Examples 1-17 and Comparative Example 1, it can be seen that adding an additive for reducing the friction coefficient to the sublayer with the highest friction coefficient in the positive electrode of a lithium-ion battery can enable the lithium-ion battery to have both higher energy density and longer cycle performance.
[0199] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and within the scope of the technical solution of the present application, any implementation method having substantially the same structure as the technical concept and exerting the same effect is included in the technical scope of the present application. In addition, without departing from the scope of the subject matter of the present application, various modifications that can be conceived by those skilled in the art to the embodiments, and other methods constructed by combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A positive electrode sheet, comprising: A positive electrode current collector and a positive electrode film layer, wherein the positive electrode film layer includes a plurality of sublayers; A first sublayer among the plurality of sublayers comprises a first positive electrode active material and an additive, and a second sublayer among the plurality of sublayers comprises a second positive electrode active material; The difference in friction coefficient between the first sub-layer and the second sub-layer is 0.1-0.3, and optionally, 0.1-0.
2.
2. The positive electrode sheet according to claim 1, wherein: The additives include at least one of magnesium stearate, talc, micro-powder silica gel, polyethylene glycol, magnesium lauryl sulfate, boron nitride, niobium diselenide, calcium fluoride and barium fluoride.
3. The positive electrode sheet according to claim 1 or 2, wherein: The difference in friction coefficient between the first positive electrode active material and the second positive electrode active material is 0.1-0.8, and optionally 0.2-0.
5.
4. The positive electrode sheet according to any one of claims 1 to 3, wherein: The friction coefficient of the first positive electrode active material is 0.8-1.5, and optionally 0.9-1.
2.
5. The positive electrode sheet according to any one of claims 1 to 4, wherein: The friction coefficient of the second positive electrode active material is 0.4-0.8, and optionally 0.5-0.
8.
6. The positive electrode sheet according to any one of claims 1 to 5, wherein: Based on 100 parts by weight of the first sub-layer, the content of the additive is 0.3-10 parts by weight, and optionally 0.5-3 parts by weight.
7. The positive electrode sheet according to any one of claims 1 to 6, wherein: The volume distribution particle size Dv99 of the additive is not greater than four fifths of the thickness of the first sub-layer.
8. The positive electrode sheet according to any one of claims 1 to 7, wherein: The volume distribution particle size Dv99 of the additive is not greater than three fifths of the volume distribution particle size Dv50 of the first positive electrode active material.
9. The positive electrode sheet according to any one of claims 1 to 8, wherein: The first sublayer is the sublayer farthest from the positive electrode current collector among the multiple sublayers.
10. The positive electrode sheet according to any one of claims 1 to 9, wherein: The mass ratio of the first sublayer to the second sublayer is 1:9-9:1, and optionally 3:7-7:
3.
11. The positive electrode sheet according to any one of claims 1 to 10, wherein: The compaction density of the positive electrode sheet is 2.0-3.5 g / cm 3 , optionally 2.5-3.2g / cm 3 .
12. The positive electrode sheet according to any one of claims 1 to 11, wherein: The compacted density of the first sublayer is 3.0-4.0 g / cm 3 , optionally 3.2-3.6 g / cm 3 .
13. The positive electrode sheet according to any one of claims 1 to 12, wherein: The compacted density of the second sublayer is 2.2-3.5 g / cm 3 , optionally 2.5-3.0g / cm 3 .
14. The positive electrode sheet according to any one of claims 1 to 13, wherein: The thickness of the positive electrode film layer is 45-100 μm, and optionally 50-85 μm.
15. The positive electrode sheet according to any one of claims 1 to 14, wherein: The thickness of the first sublayer is 5-90 μm, and optionally 20-75 μm.
16. The positive electrode sheet according to any one of claims 1 to 15, wherein: The thickness of the second sub-layer is 4-60 μm, and optionally 10-50 μm.
17. The positive electrode sheet according to any one of claims 1 to 16, wherein: The first positive electrode active material comprises a layered transition metal oxide; Optionally, including Li x (Ni a Co b Mn c ) 1-d M d O 2-y A y , wherein M includes at least one of Zr, Al, B, Ta, Mo, W, Nb, Sb, and La, 0.2<x≤1.2, 0.5≤a<1.0, 0≤b<0.5, 0≤c<1, 0≤d<1, and 0≤y<0.
02.
18. The positive electrode sheet according to any one of claims 1 to 17, wherein:The second positive electrode active material includes an olivine-structured lithium phosphate Li e Fe 1-x-y Mn x M' y P 1-m C m O 4-n D n , 0<e≤1.1, 0≤x≤1, 0≤y<1, 0≤x+y≤1, 0≤m≤0.1, 0≤n≤0.4, M' includes at least one of other transition metal elements or non-transition metal elements except Fe and Mn; Optionally, M' includes at least one of Cr, Mg, Ti, Al, Zn, W, Nb, and Zr; Optionally, the lithium-containing phosphate with an olivine structure includes at least one of lithium iron phosphate, lithium manganese phosphate, and lithium manganese iron phosphate.
19. A battery cell comprising the positive electrode sheet according to any one of claims 1 to 18.
20. A battery comprising a plurality of battery cells according to claim 19.
21. An electrical device comprising the battery as claimed in claim 20, wherein the battery is used to provide electrical energy.